Síntese de ácidos anacárdicos e análogos, candidatos a inibidores da enzima gliceraldeido-3-fosfato desidrogenase glicossomal de Trypanosoma cruzi - Pereira, Junia Motta (2007)
Chagas disease, caused by Trypanosoma cruzi, is endemic in 15 countries in Latin America, including Brazil, and it is estimated that about 16 million people are infected by this protozoan. The enzyme glyceraldehyde-3- phosphato-dehydrogenase (gGAPDH) is one of the nine enzymes involved in the T. cruzi glycolysis and experimentally it was proved that inhibition of this metabolic pathway causes the elimination of trypanosomes in the bloodstream. Among several natural products that have presented interesting inhibitory activity against this enzyme are the anacardic acids, isolated from cashew-nut shells. Many biologic and/or pharmacologic properties have been described for this class of compounds. In this work a serie of anacardic acids and analogues were synthetized and their biological activity evaluated . In total, 23 compounds were prepared and evaluated against T. cruzi gGAPDH and Schistossoma mansoni purine nucleoside phosphorylase (PNP) enzymes. In both cases the most active compound was 6-n-decylsalicylic acid with IC50 of 55 and 30 M respectively. Through the analysis of the experimental results together with the molecular dock studies, it was possible to observe that the size and substituents of alkyl side chain in these compounds can influence the inhibitory activity and the free hydroxyl groups in the ring are essential for the activity.